Lung ultrasound versus chest computed tomography for pregnant inpatients with COVID‐19. Issue 1 (11th August 2022) - Biancolin, Sckarlet Ernandes; dos Santos Fernandes, Hermann; Sawamura, Marcio Valente Yamada; Queiroz, Joelma; Centofanti, Sandra Frankfurt; Liao, Adolfo Wenjaw; da Costa Leite, Claudia; Francisco, Rossana Pulcineli Vieira; de Lourdes Brizot, Maria; ,
Abstract: Purpose: To compare lung ultrasound (US) and computed tomography (CT) in the assessment of pregnant women with COVID‐19. Methods: Prospective study comprising 39 pregnant inpatients with COVID‐19 who underwent pulmonary assessment with CT and US with a maximum span of 48 h between the exams. The thorax was divided into 12 regions and assessed in terms of the following: the presence of B‐lines (>2), coalescent B‐lines, consolidation on US; presence of interlobular thickening, ground glass, consolidation on CT. The two methods were scored by adding up the scores from each thoracic region. Results: A significant correlation was found between the scores obtained by the two methods (rICC = 0.946; p  < 0.001). They were moderately in agreement concerning the frequency of altered pulmonary regions (weighted kappa = 0.551). In US, a score over 15, coalescent B‐lines, and consolidation were predictors of the need for oxygen, whereas the predictors in CT were a lung score over 16 and consolidation. The two methods, US ( p  < 0.001; AUC = 0.915) and CT ( p  < 0.001; AUC = 0.938), were fairly accurate in predicting the need for oxygen. Conclusion: In pregnant women, lung US and chest CT are of similar accuracy in assessing lungs affected by COVID‐19 and can predict the need for oxygen. Abstract : Lung ultrasound may be satisfactorily incorporated into the obstetricians' clinical practice to evaluate pregnant women with COVID‐19. It is an alternative method which is more accessible, less expensive, faster to learn, which can be used at the bedside and repeatedly without running the risk of exposing the fetus to radiation.